Transcendence : modernity and beyond in Korean Art. - Eun-ju, Choi; Tan, Suenne Megan (Singapore : Singapore Art Museum Singapore, 2008)
Park Seo-Bo ; Lee U-Fan ; Kim, Tschang-Yeal ; Lee Jung Woong ; Lee Yong Deok ; Kim Kang-Yong ; Kim Hong-Joo ; Cheong Kwang-Ho ; Lee Lee Nam ; Suh Do Ho ; Yim Tae Kyu ; Hong Kyoung Tack ; Kang, Ik-Joong
Engels
Exhibition. Transcendence : modernity and beyond in Korean Art. Singapore. Art Museum Singapore. Singapore Art Museum Singapore. 08.11.2008 - 15.03.2009
boek
Keywords: Korea